Online Guidance Study On The Enhancement Of Completeness In Completing The Final Duties Of Distance Students - Isriyah, Mudafiatun; Degeng, I. Nyoman S.; Lasan, Blasius Boli; Muslihati (International Journal of Psychosocial Rehabilitation, 2020)
This research presented an online tutoring design that aimed to improve the completeness of completing the final assignments of distance students. The impact of online learning on aspects of intellectual maturity development was assumed to be unwise in making decisions and unskilled in solving problems. It was found in the social attendance rate of 2015. The distance students randomly selected from 70 students through the Social Attendance Scale illustrated that 42.3% of students had low Social Attendance, 28.8% moderate, and 28.9% high. The results of the data analysis showed that there were weaknesses of the distance students’ social presence that the students learned in the conditions after working because the most background of the condition was already married, the task was done quickly/instantly and depended on others. To train student self-awareness, online guidance was needed: 1) Join Together, 2) Motivating, 3) Building Commitments to Implement, 4) Observing and Evaluating. Keywords: